2008
DOI: 10.1101/gad.1697208
|View full text |Cite
|
Sign up to set email alerts
|

Mid1p/anillin and the septation initiation network orchestrate contractile ring assembly for cytokinesis

Abstract: In both animal cells and fungi, cytokinesis proceeds via a contractile actomyosin ring (CAR). Many CAR components and regulators are evolutionarily conserved. In Schizosaccharomyces pombe, the spatial cue for cytokinesis is provided by Mid1p/Anillin, whereas temporal coordination is ensured by the septation initiation network (SIN). However, neither Mid1p nor the SIN is considered to be essential for CAR assembly per se. Here, using 4D imaging, we reveal an unanticipated, novel role for the SIN in CAR assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
221
1
7

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(242 citation statements)
references
References 62 publications
13
221
1
7
Order By: Relevance
“…13 This broad band exactly reflect the early mitotic Mid1 cortical band. 8,13 The Rlc1-GFP signal then coalesces as a packed ring by lateral condensation, 9 followed by a constant diameter period and ring constriction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 This broad band exactly reflect the early mitotic Mid1 cortical band. 8,13 The Rlc1-GFP signal then coalesces as a packed ring by lateral condensation, 9 followed by a constant diameter period and ring constriction.…”
Section: Resultsmentioning
confidence: 99%
“…At mitotic commitment, nuclear Mid1 completely exits the nucleus and associates with the cell cortex prior to chromosome segregation. [2][3][4][5][6][7][8] Recent studies 9,10 have suggested a model with two parallel non overlapping mechanisms for CAR formation. 11 First, Mid1 establishes a broad band of dots that dictates the site of 'cortical nodes' formation, which are protein complexes that include Rlc1-containing myosin II hexamers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the contractile ring is formed from actomyosin filaments assembled randomly on the cortex, which eventually converge to assemble a contractile ring [Huang et al, 2008]. Contractile ring assembly is then strictly dependent on the activity of the SIN, [septation initiation network; Hachet and Simanis, 2008]. This signalling cascade, essential for cytokinesis, is activated by Plo1 kinase and controlled from the spindle pole body by the small GTPase Spg1 [Ohkura et al, 1995; Schmidt et al, 1997;Sohrmann et al, 1998; see Goyal et al, 2011 for a review].…”
Section: Mechanisms Of Contractile Ring Assemblymentioning
confidence: 99%
“…This signalling cascade, essential for cytokinesis, is activated by Plo1 kinase and controlled from the spindle pole body by the small GTPase Spg1 [Ohkura et al, 1995; Schmidt et al, 1997;Sohrmann et al, 1998; see Goyal et al, 2011 for a review]. The SIN, whose activation can bypass the requirement for Plo1 for contractile ring assembly, induces the dephosphorylation of the F-BAR protein Cdc15 [Hachet and Simanis, 2008]. Cdc15 dephosphorylation has on the other hand been shown to promote the transition from a closed to an open conformation of the molecule, allowing its oligomerization and promoting its scaffolding activity.…”
Section: Mechanisms Of Contractile Ring Assemblymentioning
confidence: 99%